A utilização dos quadrinhos no ensino de história: avanços, desafios e limites - Vilela, Marco Túlio Rodrigues (2012)
The project proposes to establish a theoretical and methodological support for the use of HQs in the teaching of History by History teachers who work in cycle 2 of elementary and high school. Through the analysis of the content of the HQs, this research will provide practical suggestions on how the comics can both be used as a documentary source for the study of a given time and can be a support material to promote in the classroom reflections on the genesis of the anachronisms found in the representations of past cultures. It seeks to identify advances and also the main difficulties, obstacles or even limits that still prevent a more frequent or useful use of this resource in the teaching of History.